Edukasi Literasi Keuangan untuk Meningkatkan Pemahaman Pengelolaan Keuangan di Yayasan Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Destian Andhani; Asep Muhammad Lutfi; Nur Rachmah Wahidah (Jurnal PKM Manajemen Bisnis, 2026)
This community service activity was conducted to improve financial literacy and enhance the understanding of financial management among teachers and educational staff at Yayasan Tajaul Karomatu, Situ Gadung Village, Tangerang Regency. The background of this activity stems from the limited knowledge and skills in managing personal and institutional finances effectively, which often leads to inefficient financial practices. The purpose of the program was to provide participants with practical knowledge and skills related to budgeting, saving, and financial planning. The PKM was carried out by seven lecturers from Universitas Pamulang on October 25, 2025. A total of 18 participants, consisting of teachers and educational staff, attended the session. The implementation method included the stages of preparation, execution, and reporting. The activities involved the presentation of materials, practical exercises, group discussions, and a question-and-answer session to ensure active participation. The results showed an increase in participants’ understanding of financial concepts and their ability to apply them in daily financial management. Participants also expressed enthusiasm and commitment to applying the acquired knowledge in their work environment. Overall, the PKM successfully achieved its objectives in fostering financial literacy and promoting responsible financial behavior.